CHARACTERISTICS OF CURRENT VARIATION IN THE COASTAL AREA OF RED RIVER DELTA - RESULTS OF RESAERCH USING THE 3D NUMERICAL MODEL - Vinh, Vu Duy; Thanh, Tran Duc (Vietnam Journal of Marine Science and Technology, 2014)
This paper presents some results of three dimension (3D) modelling application to research characteristics of field current variation in the coastal area of Red River Delta. In the study, a 3D numerical model was set up with four vertical layers (s coordinate system). The open sea boundary conditions of hydrodynamics model have been obtained by NESTING method from the same l model for the larger marine region. Hydrodynamics model was calibrated and validated by measured data of water levels in Hon Dau National Hydrographic Station and data of currents in other sites (Ba Lat and Nam Trieu). In the studied results the temporal and spatial variation of total currents  and residual currents in the coastal area of Red River Delta are obtained, in which the different roles of tidal oscillations-tide currents, fresh water from river mouths, wind stress-gradient currents and density currents were recorded (the roles of wave induced currents are ignored).